2017
DOI: 10.2754/avb201786030263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glycerol concentration on the motility of equine spermatozoa after thawing

Abstract: The aim of this study was to evaluate the effect of different glycerol concentrations on stallion sperm motility after thawing. For statistical analysis 228 ejaculates were used. The semen was filtrated to remove gel fraction; macroscopic and microscopic evaluation was done. After evaluation the ejaculates were centrifuged, the supernatant was removed and the spermatozoa were re-suspended in French diluent with different concentrations of glycerol (2.0; 2.5; 4.0 and 6.0%). The choice of concentration of glycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
(33 reference statements)
0
3
1
Order By: Relevance
“…Samples were evaluated at 60, 120 and 180 min of post-thaw incubation at different sperm and VG concentrations. This is quite different from other studies that evaluated motility indicators immediately after thawing (Macías García et al 2012;Neuhauser et al 2019) or 120 min after thawing (Olaciregui et al 2014;Mráčková et al 2017).…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…Samples were evaluated at 60, 120 and 180 min of post-thaw incubation at different sperm and VG concentrations. This is quite different from other studies that evaluated motility indicators immediately after thawing (Macías García et al 2012;Neuhauser et al 2019) or 120 min after thawing (Olaciregui et al 2014;Mráčková et al 2017).…”
Section: Discussioncontrasting
confidence: 75%
“…Because VG causes injury to spermatozoa during the cryopreservation process (Fahy et al 1990), its usage is usually limited to concentrations lower than 2.5% (Macías García et al 2012). Other studies have shown that concentrations higher than 2.5% may have better results (Mráčková et al 2017). Most of the studies were performed at relatively low sperm concentrations of 100-200 × 10 6 sperms per ml (Macías García et al 2012;Olaciregui et al 2014;Neuhauser et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations